The Influence of Individual Skills, Organizational Structure, and External Environment on the Digital Leadership of School Principals in Deli Serdang - Dea Nadhirah Mulyadi; Muhammad Fadhli (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the influence of individual skills, organizational structure, and external environment on the digital leadership of school principals in Deli Serdang Regency. The study employed a quantitative approach with a causal-associative design involving 181 junior high school principals selected through systematic sampling. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that individual skills, organizational structure, and external environment have positive and significant effects on digital leadership. Among these variables, individual skills emerged as the most dominant factor influencing principals’ digital leadership. Furthermore, the R-square value of 0.67 indicates that 67% of the variance in digital leadership can be explained by these three variables, while the remaining 33% is influenced by other factors outside the research model. These findings highlight that strengthening individual competencies, supported by adaptive organizational structures and a conducive external environment, is essential for enhancing the effectiveness of digital leadership in schools.